Panama : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This paper provides background information to the IMF staff report for the 1998 Article IV Consultation discussions with Panama. It focuses on areas of interest in Panama's medium-term economic strategy, and gives a broad overview of economic developments with emphasis on 1997. It updates information on important areas of economic activity: the structure and reform of the financial sector; reversion of the Canal Zone areas to Panama; and analysis of key elements of the economic reform program since 1994, including trade reform and other measures to foster competitiveness and competition.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet